Consumo de frutose e exercício físico, impacto na síndrome metabólica - Botezelli, Jose Diego [UNESP]; de Moura, Rodrigo Ferreira [UNESP]; Rossi, Caroline de Almeida [UNESP]; Dalia, Rodrigo Augusto [UNESP]; Cambri, Lucieli Teresa [UNESP]; Rostom de Mello, Maria Alice [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
In the last two decades, the metabolic syndrome is in focus of many health agencies worldwide. Understanding among the most important glucose intolerance and insulin resistance, other disorders have been framed in this category. The non-alcoholic hepatic steatosis appears to be one of the components of this syndrome. Several studies point to the increased consumption of fructose linked to the onset of sedentary steatohepatitis. From that premise, this review aimed to the search for studies that suggest the role of exercise as an important weapon in the treatment and prevention of non-alcoholic hepatic steatosis.

Nas ultimas duas décadas, a síndrome metabólica está em foco das diversas agencias de saúde mundiais. Compreendendo entre os aspectos mais importantes a intolerância à glicose e a resistência à insulina, outras desordens vem sendo enquadradas nessa categoria. A esteatose hepática não alcoólica emerge como um dos componentes dessa síndrome. Diversos estudos apontam o aumento do consumo de frutose associado ao sedentarismo ao aparecimento da esteatose hepática. A partir dessa premissa, a presente revisão objetivou-se na busca de estudos que apontem o papel do exercício físico como importante arma no tratamento e na prevenção da esteatose hepática não alcoólica.
Fructose Consumption and physical exercise, the impact on metabolic syndrome
Keywords: Metabolic Syndrome; Hepatic Steatosis; Physical Exercise; Fructose Consumption